Data Mining Analysis In Minimizing Company Losses Using Fuzzy Time Series Method - Saputra, Muhardi; Jones, Jones; Anderson, Wily; Ginting, Lindawati (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
Losses are the most avoided by all business entities in this case the research obtained a research study at PT. Sumatera Sarana Sekar Sakti. The company suffered a big loss in the expenditure / spending section that was not managed properly. The existence of excess funds or shortages in each company's expenditure is a form of loss, not only in the form of material but even immaterial. Therefore, this research conducts an analysis by generating data predictions so that a value is obtained that will minimize company losses because it provides the right and efficient funds. The method used in prediction is Fuzzy Time Series. It is a new category of methods that have been widely used in various studies because they produce good predictive values. In this study, the Fuzzy Time Series method produces 0.82% error rate from data analysis of 1875 company expenditure transactions. Measurement of the prediction error rate using Mean Absolute Percentage Error which is often called MAPE. It is a measurement that is often used in various studies with data prediction categories.